PERANAN KEPEMIMPINAN LURAH DALAM PEMBERDAYAAN MASYARAKAT STUDI KASUS : KELURAHAN SAMPLANGAN, KECAMATAN GIANYAR, KABUPATEN GIANYAR - Kusuma Wardani, Komang Ayu; Dewi Pascarani, Ni Nyoman; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2015)
ABSTRACT Community empowerment can be done through active community participation facilitated by the perpetrators of community empowerment. As performed by leaders in the Samplangan village, where the village chief role is to empower the people, which is evident from the absence of community development programs in the realization of direct expenditure budget from 2010 until now. The purpose of this study was to determine how the role of a village chief in empowering the community, are there external factors that affect the success of the village chief in shaping community development programs in Samplangan village. This study uses descriptive qualitative method. To obtain the data, researchers conducted observations to see directly the phenomena that occur in the field and conduct in-depth interviews with informants related to community development in the Samplangan village. Results from this study, is that community empowerment is implemented in the Samplangan village community empowerment through community organizations such as LPM, PKK, and Karang Taruna. In this empowerment, chief village provides the opportunity for people who are willing and capable to participate in any government activity. With the village chief's role as adviser, facilitator and mediator in any social institution, the ultimate goal of community empowerment in Samplangan village is that communities are able to live independently and be able to manage the potential both Human Resources or Natural Resources there can be realized. Aggressive young leaders with higher education as well as communities who want the change are factors that influence the success of a headman. By applying the type or style of charismatic leadership and democratic. Where leaders of community-oriented and provides an efficient guidance with mutual trust, giving a sense of comfort and the recognition of society. Keywords: Leadership, Community Empowerment.